HYDROCARBON RESOURCES AS AN OBJECT OF GEOPOLITICAL CONFRONTATION BETWEEN RUSSIA AND THE WEST - KHIZBULLIN, Faiz; AKHMEDINA, Gulnur; ROSTOVA, Anna; SHILINA, Svetlana (CENTRAL ASIA AND THE CAUCASUS, 2017)
Hydrocarbon resources today are a highly mythologized and increasingly politicized issue: the growing stream of contradictory information creates an ambiguous conflict-prone discourse in global geopolitics, increasing the potential for conflict in international relations. Throughout world history, the main purpose of the state has been to expand its territory in order to solve economic problems and ensure security, notably by subordinating one people to another or annexing adjacent territory. Researchers have come to the conclusion that, from a geopolitical perspective, the essence of interstate relations is a never-ending struggle between global centers of power for the possession of geographic space. Today, we can say that geopolitics has not only become a system of knowledge about control over space, but has also turned into a real tool for reformatting the world. The collapse of the bipolar geopolitical model of the world has not made the world more stable or secure. The relatively stable geopolitical structure with two world poles has given way to a period of permanent instability due to the desire of the Western powers to establish a new world order distinguished by strong unipolarity and an attempt by a certain group of industrial countries to impose their will on other states and nations. Since hydrocarbon resources are unevenly distributed around the globe, they are not only one of the main items in world trade, but also the main object of geopolitical wars. An understanding of the nature of the current geopolitical confrontation and the emergence of new forms make it necessary to study their content, identify their patterns, and assess the impact of today’s geopolitical standoff between Russia and the West on the world order as a whole. However, the fight for hydrocarbon resources, the spread of nuclear weapons, and the creation of aerospace forces with corresponding changes in the nature and forms of modern warfare give food for thought about the evolution of the inward and outward signs of geopolitical confrontation.